2008
DOI: 10.12968/bjon.2008.17.6.28904
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ experiences of privacy and dignity. Part 1: a literature review

Abstract: This article reviews the literature on patients' privacy and dignity and concludes that interest in the topic goes back to psychiatric patients in the 1960s, with the 1990s seeing a shift to all hospitals. A number of databases were used to obtain information for the literature review. Findings revealed United Kingdom (UK) government policies designed to raise the profile of patients' privacy and dignity. UK research on patients' privacy/dignity is limited, although there is universal interest. While a variety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 29 publications
3
32
0
2
Order By: Relevance
“…39,40 According to Lindwall & von Post, 41 caring can be delivered as dignified for the patients when staffs endeavor to achieve a sense of human value. Morover, Jacobs suggested that respecting human dignity is not merely a task of nurses but is fundamental to nursing care.…”
Section: Discussionmentioning
confidence: 99%
“…39,40 According to Lindwall & von Post, 41 caring can be delivered as dignified for the patients when staffs endeavor to achieve a sense of human value. Morover, Jacobs suggested that respecting human dignity is not merely a task of nurses but is fundamental to nursing care.…”
Section: Discussionmentioning
confidence: 99%
“…When the nurse is polite, friendly, helpful, empathic, respectful, and takes time for an individual human being, it preserves dignity. Similarly, it is of major importance that interaction is characterized by trust, confidentiality, and openness acknowledging individual needs (Berg & Danielson, 2007; Hanratty et al, 2012; Leung, 2009; Lohne, Aasgaard, Caspari, Sletteø, & Nåden, 2010; Matiti & Trorey, 2004, 2008; Whitehead & Wheeler, 2008; Webster & Bryan, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Although much has been written about providing care with dignity for patients (as there should be! ), [1][2][3] it is much more difficult to find literature that focuses on ensuring the clinical staff is treated with dignity. This is wrong.…”
Section: Complex Multicultural Issuesmentioning
confidence: 99%